Collaborative playbuilding and the act of crystallization. Issue 1 (1st July 2022) - Webb, James
Collaborative playbuilding is an emerging arts-based research design that uses playwriting and playbuilding as tools of inquiry for artists and researchers to investigate sociological questions, dealing with such matters as racial and class conflict, youth offenders, school safety, stereotypes of urban teenage girls, women and obesity, and social justice. Researchers use the design to generate and disseminate data; however, the literature reveals a lack of studies that show how the playbuilding process ‐ the actual structuring and crafting of the performance script ‐ can be used as a primary means of data analysis. In this article, I discuss my study, in which I used collaborative playbuilding to investigate why some African Americans leave the Black Church and choose not to return. I argue that although I conducted my research using traditional qualitative methods (i.e. interviews, questionnaires, observations and a focus group), I relied on the playbuilding process to serve as an act of crystallization, which provided me with creative distance to analyse the narrative data in interesting ways, yielding findings not previously seen in the literature and thus supporting the efficacy of the arts-based design.